How Zima Band Communicates in the Song Generasi Rapuh to Criticize Moral Degradation - Ardianto, Veri; Yatno, Tri; Setyoko, Rahmad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research was conducted to determine the meaning of social criticism in the lyrics of the song